Revision of the cirolanid isopod genus Odysseylana Malyutina, 1995 (Crustacea) with description of two new species from Singapore - Sidabalok, Conni M.; Bruce, Niel L. (Zootaxa, 2015)
The genus Odysseylana Malyutina, 1995 is revised and a new diagnosis presented; two new species from Singapore are described: Odysseylana sakijang sp. nov. and Odysseylana temasek sp. nov. The monotypic genus Parilcirolana Yu & Li, 2001, is placed in synonymy, bringing total number of species in Odysseylana to four including the type species Odysseylana sirenkoi Malyutina, 1995 and Odysseylana setosa (Yu & Li, 2001) comb. nov. The genus is known only from coastal waters from Singapore to off Macau, western Pacific. The principal distinguishing character of Odysseylana are an elongate body shape (2.9–3.5 long as greatest width), head without a rostral point, pentagonal and flat frontal lamina; antenna peduncle articles 1–3 short, 4 and 5 subequal in length and longest; and pleopod 1 peduncle quadrate, and a slender pleopod 1 endopod.